Whipple Procedure: A Five-Year Clinical Experience in Tertiary Care Center - Changazi, Shabbar H (Cureus, 2020)
Introduction: Whipple procedure is one of the major surgeries performed in tertiary care centers. Once considered a high mortality procedure is now being practicing with mortality declining to less than 5%. This study describes our five-year experience of the Whipple procedure in terms of preoperative, operative, and postoperative parameters of patients undergoing surgery in a local tertiary care setting. Material and Methods: This was a non-randomized interventional study that was conducted at the Surgical Department of Services Hospital Lahore from January 2014 to December 2018. A total of 57 Whipple procedures were performed during this period. Demographic data, presenting symptoms, physical signs, past medical history, preoperative stenting details, intra-operative duration of surgery, postoperative course and complications, pathology, and causes of postoperative death were collected on a pre-designed questionnaire. Data were entered and analyzed by using SPSS 22 (IBM Corp., Armonk, USA). Results: Out of 57 patients, 19 were females and 38 were males. The mean age of patients was 53±05 years. The most common presenting symptom was jaundice 39 (68.4%), followed by abdominal pain 32 (56.1%). The mean size of the tumor on CT-scan was 2.8±1.4 cm, the mean operation time was 315±38.3 min, mean blood loss during surgery was 500±130 ml, and mean hospital stay was 10±6 days. The major postoperative complication was the pancreatic fistula (12%). Twenty-one out of 39 patients presented with jaundice had undergone preoperative biliary stenting by endoscopic retrograde biliary stenting. The most common histological diagnosis was adenocarcinoma of pancreas 19 (33.3%). Out of 57 patients, nine (15.8%) patients expired in the first 30 days and the most frequent cause of mortality was septic shock. Conclusion: In this study, the most common presentation of patients undergoing Whipple procedure was obstructive jaundice, the most frequent operative complication was pancreatic fistula, and the most prevalent histopathology was carcinoma of the pancreas. Perioperative parameters such as mean operative time, mean blood loss during surgery, and mean length of hospital stay were comparable with other studies. However, mortality in this study was slightly higher. It can be concluded that with meticulous surgical technique, securing hemostasis strictly and standard critical care postoperatively can decrease morbidity and mortality after the Whipple procedure.